2013
DOI: 10.1161/hypertensionaha.111.00633
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nervous System and Hypertension

Abstract: With the development and implementation of device-based therapeutic interventions to decrease renal and systemic nerve activity in patients with resistant hypertension, there has been an increase in research dealing with the role of the sympathetic nervous system in hypertension. These interventions have produced substantial decreases in blood pressure in patients wherein pharmacological treatments, including agents which inhibit the effects of the renin-angiotensin-aldosterone system, have failed serves to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(119 citation statements)
references
References 31 publications
3
111
0
5
Order By: Relevance
“…This suggests that the sympathoinhibition may play a role in the favorable cardiovascular and metabolic effects of this therapeutic procedure reported in previous studies [5][6][7]10 and largely confirmed in the present one. This is not unexpected because the importance of sympathetic hyperactivity in the pathogenesis of hypertension is well documented [32][33][34] and so is, both in experimental animals and in man, its stimulating influence on leptin and insulin secretion, [35][36][37] as well as its ability to cause or worsen insulin resistance. 18,19 In the case of leptin, however, prevailing evidence suggests that the opposite is also true, namely that leptin may trigger central and peripheral sympathoexcitation.…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that the sympathoinhibition may play a role in the favorable cardiovascular and metabolic effects of this therapeutic procedure reported in previous studies [5][6][7]10 and largely confirmed in the present one. This is not unexpected because the importance of sympathetic hyperactivity in the pathogenesis of hypertension is well documented [32][33][34] and so is, both in experimental animals and in man, its stimulating influence on leptin and insulin secretion, [35][36][37] as well as its ability to cause or worsen insulin resistance. 18,19 In the case of leptin, however, prevailing evidence suggests that the opposite is also true, namely that leptin may trigger central and peripheral sympathoexcitation.…”
Section: Discussionmentioning
confidence: 93%
“…1,2 Fibrosis is estimated to contribute to 45% of all causes of mortality 3 and is promoted by many factors present in damaged kidneys and CKD, including oxidative stress, inflammation, hypertension, hypoxia, metabolic toxins, and activation of the sympathetic nervous system (SNS). [4][5][6][7][8][9][10][11][12] The association of hypertensive renal disease with dietary salt is well recognized. [13][14][15][16] Many patients with CKD have salt-sensitive hypertension.…”
mentioning
confidence: 99%
“…5,6 Moreover, ≈15% of all hypertensive patients have resistant hypertension, and fail to achieve blood pressure goals, despite 3 or more antihypertensive medications. [7][8][9] Because the renal sympathetic nervous system is considered to be essential for the development of arterial hypertension, 10,11 renal sympathetic denervation using catheter-based radiofrequency ablation is a promising new option for patients suffering resistant hypertension. However, the arterial wall injury induced by radiofrequency energy remains a concern, because radiofrequency has been shown to acutely induce luminal thrombus deposition and late stenosis of the renal artery (RA).…”
mentioning
confidence: 99%